The M&A Behavior of Family Firms - Jinhao Shu (Junior Management Science (JUMS), 2021)
The present study aims to identify the driving acquisition goals of family firms' acquisitions and analyse the role of innovation in these acquisitions. Therefore, the study deploys a qualitative approach investigating 15 German family firms to derive patterns within the qualitative data. As a result, the study proposes 14 propositions, which mainly suggest a co-existence of multiple goals in acquisitions. Similarly, the propositions argue that the goals related to the categories of expansion, market competitiveness and innovation are decisively driving the acquisitions undertaken by family firms. The study further proposes that the acquisition of innovation is a critical key to the success of family firms and a means to an end for achieving other related goals such as the survival of family firms. Beyond getting a broader understanding of the acquisitions made by family firms, the study shows further avenues for research in the field of family firms' M&A activities.
Keywords: 650; Family Firm; Innovation; Mergers & Acquisitions; Drivers of Mergers & Acquisitions; Acquisitions Motives; Acquisition Goals; Innovation in Mergers & Acquisitions